The war against domestic violence - Ross, Lee E. (CRC Press)
An overview of intimate partner violence among Latinos / Joanne Klevens -- Domestic violence in the African American community : moving forward to end abuse / Tricia B. Bent-Goodley -- Domestic violence in Asian cultures / Qiang Xu and Allen Anderson -- Domestic violence among Native Americans / Julie C. Abril -- Domestic violence in Sub-Saharan Africa / Godpower O. Ok ereke, Peter Racheotes, and Josephine Kahler -- Physical child abuse, neglect, and domestic violence : a case studies approach / Mark A. Winton and Elizabeth M. Rash -- The response of child welfare agencies to domestic violence / Melanie Shepard and Gina Farrell